Galectins as modulators of tumour progression - Liu, Fu Tong (2005)
Galectins are a family of animal lectins with diverse biological activities. They function both extracellularly, by interacting with cell-surface and extracellular matrix glycoproteins and glycolipids, and intracellularly, by interacting with cytoplasmic and nuclear proteins to modulate signalling pathways. Current research indicates that galectins have important roles in cancer; they contribute to neoplastic transformation, tumour cell survival, angiogenesis and tumour metastasis. They can modulate the immune and inflammatory responses and might have a key role helping tumours to escape immune surveillance. How do the different members of the Galectin family contribute to these diverse aspects of tumour biology?